A method for synthesizing hollow lithium iron phosphate spheres by solid phase method and high-performance lithium battery
Synthesis of lithium iron phosphate materials with hollow spherical structures by solid phase method solves the problem that it is difficult to synthesize high-performance spherical lithium iron phosphate materials at low cost in the prior art, and achieves the high electrochemical performance and rate performance of lithium batteries.
Patent Information
- Application Number
- CN202110775829.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-07-08
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-07-08
AI Technical Summary
It is difficult for the prior art to synthesize high-performance spherical lithium iron phosphate materials through low-cost solid phase methods, and it is difficult for traditional methods to achieve the formation of hollow spherical structures, affecting the electrochemical performance of the material.
The precursor is prepared by mixing the lithium source, iron source, phosphorus source and carbon source, and calcined at high temperature. The solid phase method is used to synthesize lithium iron phosphate material with hollow spherical structure.
The high-performance hollow ball lithium iron phosphate material is synthesized through low-cost solid phase method, providing a fast lithium ion migration channel, significantly improving the electrochemical performance and rate performance of lithium batteries.
Smart Images

Figure CN115602833B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and in particular relates to a method for synthesizing hollow lithium iron phosphate balls by a solid phase method and a high-performance lithium battery. Background Art
[0002] Lithium-ion batteries have revolutionized energy storage technology and play a very important role in the development of chemical power sources. The electrochemical performance of lithium-ion battery cathode materials can fully affect the performance of the entire lithium-ion battery. Among cathode materials, lithium cobalt oxide (LiCoO2) occupies the main market of portable electronic products, but cobalt resources are scarce, expensive, and their application areas are limited; ternary materials (NCM, NCA) have been widely used in the field of new energy electric vehicles, but their safety is not high enough; lithium iron phosphate (LiFePO4) with a slightly lower discharge platform has outstanding safety, environmental friendliness and low cost, and is a very potential development target.
[0003] Spherical lithium iron phosphate materials usually have excellent electrochemical performance. Traditional spherical lithium iron phosphate particles are often synthesized by hydrothermal method, solvothermal method, sol-gel method and spray drying method. However, most industries use low-cost solid-phase method to synthesize lithium iron phosphate. It is easier to accept and promote the synthesis of high-performance materials using low-cost routes. Therefore, it is expected that the preparation of spherical lithium iron phosphate materials based on template-free additive solid-phase method can be realized by screening materials. Summary of the invention
[0004] The purpose of the present invention is to provide a solid phase synthesis method of hollow lithium iron phosphate spheres and a lithium battery with high rate performance can be obtained by using the hollow lithium iron phosphate sphere material prepared by the method.
[0005] The purpose of the present invention is achieved through the following technical solutions:
[0006] The solid phase synthesis method of lithium iron phosphate hollow spheres comprises mixing a lithium source, an iron source, a phosphorus source and a carbon source to obtain a precursor; and calcining the precursor at a high temperature to obtain a lithium iron phosphate material having a hollow sphere structure.
[0007] Optionally, the lithium source used for solid phase synthesis of lithium iron phosphate hollow spheres is one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium nitrate, and lithium phosphate.
[0008] Optionally, the iron source used for solid phase synthesis of hollow lithium iron phosphate spheres is one or more of ferrous oxalate, ferrous carbonate, ferrous gluconate, ferric nitrate, and ferric phosphate.
[0009] Optionally, the phosphorus source used for solid phase synthesis of hollow lithium iron phosphate spheres is one or more of ammonium dihydrogen phosphate, ammonium phosphate, ammonium polyphosphate, diammonium hydrogen phosphate, lithium dihydrogen phosphate, and dilithium hydrogen phosphate.
[0010] Optionally, the carbon source used for solid phase synthesis of hollow lithium iron phosphate spheres is one or more of glucose, sucrose, citric acid, polyethylene glycol, polyvinyl alcohol, starch, polyvinylidene fluoride, acetylene black, and carbon black.
[0011] Optionally, the method for mixing materials for solid phase synthesis of hollow lithium iron phosphate spheres is one or more of wet high energy ball milling, dry high energy ball milling, wet planetary ball milling, dry planetary ball milling, and grinding.
[0012] A high-performance lithium battery comprises a positive electrode and a negative electrode, wherein the positive electrode is a hollow spherical lithium iron phosphate material prepared by the method according to any one of claims 1 to 6.
[0013] Optionally, the negative electrode material is one of graphite, carbon-silicon composite material, metallic lithium, graphene, graphene oxide, and lithium titanate.
[0014] It can be seen from the above technical scheme that the present invention optimizes the low-cost solid-phase synthesis steps, introduces polymer raw materials into the synthesis of traditional lithium iron phosphate materials based on the cohesive behavior of polymers under temperature fields, and prepares lithium iron phosphate with a hollow sphere structure. The hollow sphere structure of lithium iron phosphate can provide a fast lithium ion migration channel and exhibits excellent electrochemical behavior. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 The scanning electron microscope morphology comparison diagram of the lithium iron phosphate materials prepared in Example 1 and Comparative Examples 1 to 3 is shown.
[0016] Figure 2 This is a scanning electron microscope morphology image of the cross section of the lithium iron phosphate material prepared in Example 1.
[0017] Figure 3 The scanning electron microscope morphology comparison diagram of the lithium iron phosphate materials prepared in Example 1, Comparative Example 4 and Comparative Example 5 is shown.
[0018] Figure 4 The constant current charge-discharge cycle performance comparison chart of the lithium battery assembled in Example 6 and the lithium batteries assembled in Comparative Examples 8 to 10 at a rate of 0.1C is shown.
[0019] Figure 5 This is a comparison chart of the constant current charge and discharge cycle performance of the lithium battery assembled in Example 6 and the lithium batteries assembled in Comparative Examples 11 and 12 at a constant current charge and discharge rate of 0.1C.
[0020] Figure 6 This is a comparison diagram of the electrochemical impedance of the lithium battery assembled in Example 6 and the lithium battery assembled in Comparative Example 8.
[0021] Figure 7 This is a comparison diagram of the cyclic voltammetry of the lithium battery assembled in Example 6 and the lithium battery assembled in Comparative Example 8.
[0022] Figure 8 This is a comparison chart of the constant current charge and discharge cycle performance of the lithium battery assembled in Example 6 and the lithium batteries assembled in Comparative Examples 8, 11 and 12 at a 10C rate.
[0023] The specific implementation modes of the present invention are further described in detail below with reference to the accompanying drawings. DETAILED DESCRIPTION
[0024] In order to more clearly demonstrate the above and other purposes, features and advantages of the present invention, the embodiments of the present invention are described in detail below, but they are not intended to limit the invention in any way.
[0025] The idea of the present invention is to mix a lithium source, an iron source, a phosphorus source and a carbon source to obtain a precursor; and calcine the precursor at a high temperature to obtain a lithium iron phosphate material with a hollow sphere structure.
[0026] The lithium source used for the solid phase synthesis of hollow lithium iron phosphate spheres in the present invention is one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium nitrate and lithium phosphate.
[0027] The iron source used for solid phase synthesis of hollow lithium iron phosphate spheres in the present invention is one or more of ferrous oxalate, ferrous carbonate, ferrous gluconate, ferric nitrate and ferric phosphate.
[0028] The phosphorus source used for solid phase synthesis of hollow lithium iron phosphate spheres in the present invention is one or more of diammonium phosphate, ammonium phosphate, ammonium polyphosphate, diammonium hydrogen phosphate, lithium dihydrogen phosphate and dilithium hydrogen phosphate.
[0029] The carbon source used for solid phase synthesis of hollow lithium iron phosphate spheres in the present invention is one or more of glucose, sucrose, citric acid, polyethylene glycol, polyvinyl alcohol, starch, polyvinylidene fluoride, acetylene black and carbon black.
[0030] The present invention is used for
[0031] The method for mixing materials for synthesizing hollow lithium iron phosphate balls by solid phase method is one or more of wet high energy ball milling, dry high energy ball milling, wet planetary ball milling, dry planetary ball milling, and grinding.
[0032] When the battery is assembled using the aforementioned lithium iron phosphate hollow sphere material, the negative electrode material can be graphite, carbon-silicon composite material, metallic lithium, graphene, graphene oxide, or lithium titanate.
[0033] The present invention is further described below by specific examples and comparative examples. Unless otherwise specified, the reagents, materials and instruments used in the following are conventional reagents, conventional materials and conventional instruments, which can be purchased through normal channels.
[0034] Embodiment 1:
[0035] In this embodiment, the lithium source is lithium carbonate, the iron source is ferrous oxalate, the phosphorus source is ammonium polyphosphate, and the carbon source is glucose and polyethylene glycol:
[0036] Lithium carbonate, ferrous oxalate, ammonium polyphosphate, glucose and polyethylene glycol were mixed in a molar ratio of 0.5:1:1.2:0.1:0.1, and ground in a mortar;
[0037] The above mixture was subjected to wet high-energy ball milling for 2 h;
[0038] The material mixed by high-energy ball milling was transferred to an oven at 80°C for drying;
[0039] The dried material was transferred to a tube furnace and calcined at 650° C. in an argon atmosphere for 4 h to obtain the product lithium iron phosphate hollow sphere material.
[0040] Embodiment 2:
[0041] In this embodiment, the lithium source is lithium carbonate, the iron source is ferrous oxalate, the phosphorus source is ammonium polyphosphate, and the carbon source is glucose and polyethylene glycol:
[0042] Lithium carbonate, ferrous oxalate, ammonium polyphosphate, glucose and polyethylene glycol were mixed in a molar ratio of 0.5:1:1.2:0.1:0.1, and ground in a mortar;
[0043] The above mixture was subjected to dry high-energy ball milling for 2 h;
[0044] The material mixed by high-energy ball milling was transferred to an oven at 80°C for drying;
[0045] The dried material was transferred to a tubular furnace and calcined at 650° C. in an argon atmosphere for 4 h to obtain the product lithium iron phosphate material.
[0046] Embodiment 3:
[0047] In this embodiment, the lithium source is lithium carbonate, the iron source is ferrous oxalate, the phosphorus source is ammonium polyphosphate, and the carbon source is glucose and polyethylene glycol:
[0048] Lithium carbonate, ferrous oxalate, ammonium polyphosphate, glucose and polyethylene glycol were mixed in a molar ratio of 0.5:1:1.2:0.1:0.1, and ground in a mortar;
[0049] The above mixture was subjected to wet planetary ball milling for 2 h;
[0050] The material mixed by planetary ball mill was transferred to an oven at 80°C for drying;
[0051] The dried material was transferred to a tubular furnace and calcined at 650° C. in an argon atmosphere for 4 h to obtain the product lithium iron phosphate material.
[0052] Embodiment 4:
[0053] In this embodiment, the lithium source is lithium carbonate, the iron source is ferrous oxalate, the phosphorus source is ammonium polyphosphate, and the carbon source is glucose and polyethylene glycol:
[0054] Lithium carbonate, ferrous oxalate, ammonium polyphosphate, glucose and polyethylene glycol were mixed in a molar ratio of 0.5:1:1.2:0.1:0.1, and ground in a mortar;
[0055] The above mixture was subjected to dry planetary ball milling for 2 h;
[0056] The material mixed by planetary ball mill was transferred to an oven at 80°C for drying;
[0057] The dried material was transferred to a tubular furnace and calcined at 650° C. in an argon atmosphere for 4 h to obtain the product lithium iron phosphate material.
[0058] Embodiment 5:
[0059] In this embodiment, the lithium source is lithium carbonate, the iron source is ferrous oxalate, the phosphorus source is ammonium polyphosphate, and the carbon source is glucose and polyethylene glycol:
[0060] Lithium carbonate, ferrous oxalate, ammonium polyphosphate, glucose and polyethylene glycol were mixed in a molar ratio of 0.5:1:1.2:0.1:0.1 and ground in a mortar for 0.5 h;
[0061] The ground and mixed materials were transferred to an oven at 80°C for drying;
[0062] The dried material was transferred to a tubular furnace and calcined at 650° C. in an argon atmosphere for 4 h to obtain the product lithium iron phosphate material.
[0063] Embodiment 6:
[0064] The hollow spherical lithium iron phosphate material prepared in Example 1 was used to assemble a lithium-ion battery using a conventional assembly process, wherein the loading amount of the lithium iron phosphate positive electrode material was 2 mg cm -2 The separator is a 20μm thick polypropylene separator and the negative electrode uses metallic lithium.
[0065] Embodiment 7:
[0066] The lithium iron phosphate material prepared in Example 3 was used to assemble a lithium-ion battery using a conventional assembly process, wherein the loading amount of the lithium iron phosphate positive electrode material was 2 mg cm -2 The separator is a 20μm thick polypropylene separator and the negative electrode uses metallic lithium.
[0067] Embodiment 8:
[0068] The lithium iron phosphate material prepared in Example 5 was used to assemble a lithium-ion battery using a conventional assembly process, wherein the loading amount of the lithium iron phosphate positive electrode material was 2 mg cm -2 The separator is a 20μm thick polypropylene separator and the negative electrode uses metallic lithium.
[0069] Comparative Example 1:
[0070] The difference between Comparative Example 1 and Example 1 is that when preparing the lithium iron phosphate material, the phosphorus source is replaced with ammonium dihydrogen phosphate.
[0071] Comparative Example 2:
[0072] The difference between Comparative Example 2 and Example 1 is that when preparing the lithium iron phosphate material, the carbon source is changed to a single glucose carbon source.
[0073] Comparative Example 3:
[0074] The difference between Comparative Example 3 and Example 1 is that when preparing the lithium iron phosphate material, the carbon source is changed to a single polyethylene glycol carbon source.
[0075] Comparative Example 4:
[0076] The difference between Comparative Example 4 and Example 1 is that the wet high energy time for preparing lithium iron phosphate material is extended to 4 hours.
[0077] Comparative Example 5:
[0078] The difference between Comparative Example 5 and Example 1 is that the wet high energy time for preparing the lithium iron phosphate material is extended to 6 hours.
[0079] Comparative Example 6:
[0080] The difference between Comparative Example 6 and Example 1 is that the calcination temperature when preparing the lithium iron phosphate material is 600°C.
[0081] Comparative Example 7:
[0082] The difference between Comparative Example 7 and Example 1 is that the calcination temperature when preparing the lithium iron phosphate material is 700°C.
[0083] Comparative Example 8
[0084] The lithium iron phosphate material prepared in Comparative Example 1 was used to assemble a lithium-ion battery using a conventional assembly process, wherein the loading amount of the lithium iron phosphate positive electrode material was 2 mg cm -2 The separator is a 20μm thick polypropylene separator and the negative electrode uses metallic lithium.
[0085] Comparative Example 9
[0086] The lithium iron phosphate material prepared in Comparative Example 2 was used to assemble a lithium-ion battery using a conventional assembly process, wherein the loading amount of the lithium iron phosphate positive electrode material was 2 mg cm -2 The separator is a 20μm thick polypropylene separator and the negative electrode uses metallic lithium.
[0087] Comparative Example 10
[0088] The lithium iron phosphate material prepared in Comparative Example 3 was used to assemble a lithium-ion battery using a conventional assembly process, wherein the loading amount of the lithium iron phosphate positive electrode material was 2 mg cm -2 The separator is a 20μm thick polypropylene separator and the negative electrode uses metallic lithium.
[0089] Comparative Example 11
[0090] The lithium iron phosphate material prepared in Comparative Example 4 was used to assemble a lithium-ion battery using a conventional assembly process, wherein the loading amount of the lithium iron phosphate positive electrode material was 2 mg cm -2 The separator is a 20μm thick polypropylene separator and the negative electrode uses metallic lithium.
[0091] Comparative Example 12
[0092] The lithium iron phosphate material prepared in Comparative Example 5 was used to assemble a lithium-ion battery using a conventional assembly process, wherein the loading amount of the lithium iron phosphate positive electrode material was 2 mg cm -2 The separator is a 20μm thick polypropylene separator and the negative electrode uses metallic lithium.
[0093] The materials prepared in Example 1 and Comparative Examples 1 to 5 were subjected to scanning electron microscopy testing, the cross-section of the material prepared in Example 1 was subjected to scanning electron microscopy testing, the batteries assembled in Example 6 and Comparative Examples 8 to 12 were characterized by constant current charge and discharge, the batteries assembled in Example 6 and Comparative Example 8 were subjected to electrochemical impedance testing, and the batteries assembled in Example 6 and Comparative Example 8 were subjected to cyclic voltammetry testing.
[0094] Figure 1 The scanning electron microscope morphology comparison diagram of the lithium iron phosphate materials prepared in Example 1 and Comparative Examples 1 to 3 is shown in FIG. Figure 1It can be seen that the lithium iron phosphate materials prepared in Example 1 and Comparative Example 2 are spherical particles, and the lithium iron phosphate materials prepared in Comparative Example 1 and Comparative Example 3 are block particles, indicating that the phosphorus source and the carbon source have an effect on the formation of spherical particles.
[0095] Figure 2 is a scanning electron microscope image of the cross section of the lithium iron phosphate material prepared in Example 1. Figure 2 It can be seen that the spherical particles in Example 1 are hollow structures.
[0096] Figure 3 The scanning electron microscope morphology comparison diagram of the lithium iron phosphate materials prepared in Example 1, Comparative Example 4 and Comparative Example 5 is shown in FIG. Figure 3 It can be seen that the lithium iron phosphate materials prepared in Example 4 and Comparative Example 5 are block particles, indicating that the time of wet high-energy ball milling has an effect on the formation of spherical particles.
[0097] Figure 4 The constant current charge-discharge cycle performance comparison diagram of the lithium battery assembled in Example 6 and the lithium battery assembled in Comparative Examples 8 to 10 at a rate of 0.1C is shown in FIG. Figure 4 It can be seen that the specific capacity of the lithium battery assembled in Example 6 reaches 163 mAh g at a rate of 0.1C. -1 The lithium battery assembled in Comparative Example 8 has a specific capacity of 159 mAh g at a rate of 0.1C. -1 The lithium battery assembled in Comparative Example 9 has a specific capacity of 158 mAh g at a rate of 0.1C. -1 The lithium battery assembled in Comparative Example 10 has a specific capacity of 160 mAh g at a rate of 0.1C. -1 , indicating that the hollow sphere structured lithium iron phosphate positive electrode material in Example 6 has the best charge and discharge performance.
[0098] Figure 5 The constant current charge-discharge cycle performance comparison diagram of the lithium battery assembled in Example 6 and the lithium batteries assembled in Comparative Examples 11 and 12 at a rate of 0.1C is shown in FIG. Figure 5 It can be seen that the lithium battery assembled in ratio 11 has a specific capacity of 153 mAh g at a rate of 0.1C. -1 The lithium battery assembled in Comparative Example 12 has a specific capacity of 158 mAh g at a rate of 0.1C. -1 , indicating that materials with hollow sphere structure are beneficial to the charge and discharge performance of the material.
[0099] Figure 6 is a comparison diagram of the electrochemical impedance of the lithium battery assembled in Example 6 and the lithium battery assembled in Comparative Example 8, Figure 6It can be seen that the impedance curve of the lithium battery assembled in Example 6 has a smaller impedance than the impedance curve of the lithium battery assembled in Comparative Example 8, indicating that the lithium iron phosphate material with a hollow sphere structure has better dynamics.
[0100] Figure 7 is a cyclic voltammetry comparison diagram of the lithium battery assembled in Example 6 and the lithium battery assembled in Comparative Example 8, Figure 7 It can be seen that the difference in the redox peak position of the cyclic voltammetry curve of the lithium battery assembled in Example 6 is smaller than that of the cyclic voltammetry curve of the lithium battery assembled in Comparative Example 8, indicating that the hollow sphere structured lithium iron phosphate material has better reversibility.
[0101] Figure 8 : is a comparison chart of the constant current charge-discharge cycle performance of the lithium battery assembled in Example 6 and the lithium batteries assembled in Comparative Examples 8, 11 and 12 at a rate of 10C, Figure 8 It can be seen that the specific capacity of the lithium battery assembled in Example 6 reaches 123 mAh g at a rate of 10C. -1 The lithium battery assembled in Comparative Example 8 has a specific capacity of 107 mAh g at a rate of 10C. -1 The lithium battery assembled in Comparative Example 11 has a specific capacity of 101 mAh g at a rate of 10C. -1 The lithium battery assembled in Comparative Example 10 has a specific capacity of 100 mAh g at a rate of 10C. -1 , indicating that the hollow sphere structured lithium iron phosphate positive electrode material in Example 6 has the best rate performance.
[0102] The present invention is not limited to the above-mentioned embodiments. On the basis of the technical solution disclosed in the present invention, technicians in this field can make some substitutions and deformations to some technical features therein according to the disclosed technical content without creative labor, and these substitutions and deformations are all within the protection scope of the present invention.
Claims
1. A method for synthesizing hollow lithium iron phosphate spheres by a solid phase method, characterized in that: The method comprises the following steps: mixing a lithium source, an iron source, a phosphorus source and a carbon source to obtain a precursor; calcining the precursor at a high temperature to obtain a lithium iron phosphate material having a hollow sphere structure; The phosphorus source is ammonium polyphosphate; The carbon sources are glucose and polyethylene glycol.
2. The method for synthesizing hollow lithium iron phosphate spheres by a solid phase method as claimed in claim 1, characterized in that: The lithium source is one or more of lithium carbonate, lithium hydroxide, lithium acetate, lithium nitrate and lithium phosphate.
3. The method for synthesizing hollow lithium iron phosphate spheres by solid phase method according to claim 1, characterized in that: The iron source is one or more of ferrous oxalate, ferrous carbonate, ferrous gluconate, ferric nitrate and ferric phosphate.
4. The method for synthesizing hollow lithium iron phosphate spheres by solid phase method according to claim 1, characterized in that: The method of mixing the materials is one or more of wet high-energy ball milling, dry high-energy ball milling, wet planetary ball milling, dry planetary ball milling, and grinding.
5. High performance lithium battery, including: The positive electrode and the negative electrode are characterized in that the positive electrode is a hollow spherical lithium iron phosphate material prepared by the method according to any one of claims 1 to 4.
6. The high performance lithium battery according to claim 5, characterized in that: The negative electrode material is one of graphite, carbon-silicon composite material, metallic lithium, graphene, graphene oxide or lithium titanate.
Citation Information
Patent Citations
Spherical cathode material for lithium-ion secondary battery and preparation method of spherical cathode material
CN105552370A